Application of Alternative Floor Space Prediction Equations using Microsoft Excel® - J. R. Flohr; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
The following information is related to the use of a spreadsheet tool designed to estimate the growth rate of finishing pigs provided varying floor space allowances. The spreadsheet is broken into four sections: 1) the adjustment observation section, 2) the estimate input section, 3) the database range information, and 4) the predicted performance output. Sections 1 and 2 allow users to input information to adjust the prediction equations to specific herd growth rates as well as information needed to calculate the growth rate estimates for different floor space allowances. This tool allows producers to utilize the prediction equations without having to convert standard to metric units and provides a simple output that is easy to evaluate and use as compared to the more complex prediction equations themselves. Three examples are included to show users the possible value of the spreadsheet tool. It is important for users to understand the potential pitfalls associated with inputting information into the spreadsheet and formatting “flags” that warn users of potential problems in the input information.
Keywords: finishing pigs; floor space; prediction equations